Wholesale justice: constitutional democracy and the problem of the class action lawsuit - Redish, Martin H. (Stanford Law Books, 2009)
"Law students generally learn that the class action is a complex joinder device that can serve as a powerful check on governmental or corporate excess or illegality. It is unlikely, however, that they are ... asked to view the class action device from the broader perspectives of constitutional or political theory. The purpose of this book is to undertake just such an inquiry, and to draw a number of valuable lessons for the structure and viability of the modern class action"--Introduction, page 2